A family history of knee joint replacement increases the progression of knee radiographic osteoarthritis and medial tibial cartilage volume loss over 10 years. Issue 2 (February 2015) - Khan, H.I.; Aitken, D.; Chou, L.; McBride, A.; Ding, C.; Blizzard, L.; Pelletier, J.-P.; Pelletier, J.M.; Cicuttini, F.; Jones, G.
Summary: Objectives: Osteoarthritis (OA) has a genetic component but it is uncertain if the offspring of those with knee OA are at a greater risk. The aim of this study was to describe radiographic OA (ROA) progression and cartilage loss over 10 years in a midlife cohort with some having a family history of OA and some community based controls. Methods: 220 participants [mean-age 45 (26–61); 57% female] were studied at baseline and 10 years. Half were adult offspring of subjects who underwent knee replacement for OA and the remainder were randomly selected controls. Joint space narrowing (JSN) and osteophytes were assessed on radiographs and cartilage volume (tibial, femoral and patellar), cartilage defects, bone marrow lesions (BMLs) and meniscal tears were assessed on Magnetic resonance imaging (MRI). Results: For ROA, there was a significant difference between offspring and controls in unadjusted analysis for change in total ROA, medial JSN, total medial, total lateral and total osteophyte scores. This difference persisted for medial JSN (difference in ratios = +1.93 (+1.04,  +3.51) ) only, after adjustment for confounders and baseline differences. In unadjusted analysis for cartilage loss, offspring lost more cartilage at the medial tibial (difference in means = −79.13 (−161.92, +3.71)) site only. This difference became of borderline significance after adjustment for baseline differences ( P  = 0.055). Conclusion: The offspring of subjects having a total knee replacement have a greater worsening of ROA (both JSN and osteophytes) and higher medial tibial cartilage volume loss over 10 years. Most of these changes are mediated by differences in baseline characteristics of offspring and controls except for increase in medial JSN.